Unsaturated Fatty Acid, cis-2-Decenoic Acid, in Combination with Disinfectants or Antibiotics Removes Pre-Established Biofilms Formed by Food-Related Bacteria - Sepehr, Shayesteh; Rahmani-Badi, Azadeh; Babaie-Naiej, Hamta; Soudi, Mohammad Reza (PLOS ONE, 2014)
Biofilm formation by food-related bacteria and food-related pathogenesis are significant problems in the food industry. Even though much disinfection and mechanical procedure exist for removal of biofilms, they may fail to eliminate pre-established biofilms. cis-2 decenoic acid (CDA), an unsaturated fatty acid messenger produced by Pseudomonas aeruginosa, is reportedly capable of inducing the dispersion of established biofilms by multiple types of microorganisms. However, whether CDA has potential to boost the actions of certain antimicrobials is unknown. Here, the activity of CDA as an inducer of pre-established biofilms dispersal, formed by four main food pathogens; Staphylococcus aureus, Bacillus cereus, Salmonella enterica and E. coli, was measured using both semi-batch and continuous cultures bioassays. To assess the ability of CDA combined biocides treatments to remove pre-established biofilms formed on stainless steel discs, CFU counts were performed for both treated and untreated cultures. Eradication of the biofilms by CDA combined antibiotics was evaluated using crystal violet staining. The effect of CDA combined treatments (antibiotics and disinfectants) on biofilm surface area and bacteria viability was evaluated using fluorescence microscopy, digital image analysis and LIVE/DEAD staining. MICs were also determined to assess the probable inhibitory effects of CDA combined treatments on the growth of tested microorganisms' planktonic cells. Treatment of pre-established biofilms with only 310 nM CDA resulted in at least two-fold increase in the number of planktonic cells in all cultures. While antibiotics or disinfectants alone exerted a trivial effect on CFU counts and percentage of surface area covered by the biofilms, combinational treatments with both 310 nM CDA and antibiotics or disinfectants led to approximate 80% reduction in biofilm biomass. These data suggests that combined treatments with CDA would pave the way toward developing new strategies to control biofilms with widespread applications in industry as well as medicine.